Enhanced conflict-driven cognitive control by emotional arousal, not by valence. Issue 6 (18th August 2017) - Zeng, Qinghong; Qi, Senqing; Li, Miaoyun; Yao, Shuxia; Ding, Cody; Yang, Dong
ABSTRACT: Emotion is widely agreed to have two dimensions, valence and arousal. Few studies have explored the effect of emotion on conflict adaptation by considering both of these, which could have dissociate influence. The present study aimed to fill the gap as to whether emotional valence and arousal would exert dissociable influence on conflict adaptation. In the experiments, we included positive, neutral, and negative conditions, with comparable arousal between positive and negative conditions. Both positive and negative conditions have higher arousal than neutral ones. In Experiment 1, by using a two-colour-word Flanker task, we found that conflict adaptation was enhanced in both positive and negative contexts compared to a neutral context. Furthermore, this effect still existed when controlling stimulus–response repetitions in Experiment 2, which used a four-colour-word Flanker task. The findings suggest emotional arousal enhances conflict adaptation, regardless of emotional valence. Thus, future studies should consider emotional arousal when studying the effect of emotion on conflict adaptation. Moreover, the unique role of the emotional context in conflict-driven cognitive control is emphasised.